An extreme-mass ratio, short-period eclipsing binary consisting of a B dwarf primary and a pre-main-sequence M star companion discovered by KELT. Issue 3 (12th October 2020) - Stevens, Daniel J; Zhou, George; Johnson, Marshall C; Rizzuto, Aaron C; Rodriguez, Joseph E; Bieryla, Allyson; Collins, Karen A; Villanueva, Steven; Wright, Jason T; Gaudi, B Scott; Latham, David W; Beatty, Thomas G; et al.
ABSTRACT: We present the discovery of KELT J072709 + 072007 (HD 58730), a very low mass ratio ( q ≡ M 2 / M 1 ≈ 0.07) eclipsing binary (EB) identified by the Kilodegree Extremely Little Telescope (KELT) survey. We present the discovery light curve and perform a global analysis of four high-precision ground-based light curves, the Transiting Exoplanets Survey Satellite ( TESS ) light curve, radial velocity (RV) measurements, Doppler Tomography (DT) measurements, and the broad-band spectral energy distribution. Results from the global analysis are consistent with a fully convective ($M_2 = 0.22 ± 0.02\ \, M_{\odot })$ M star transiting a late-B primary ($M_1 = 3.34^{+0.07}_{-0.09}\ \, M_{\odot }\, and\, \ T_{\rm eff, 1} = 11960^{+430}_{-520}\ {\rm K}$ ). We infer that the primary star is $183_{-30}^{+33}$ Myr old and that the companion star's radius is inflated by $26 ± 8{{\ \rm per\ cent}}$ relative to the predicted value from a low-mass isochrone of similar age. We separately and analytically fit for the variability in the out-of-eclipse TESS phase curve, finding good agreement between the resulting stellar parameters and those from the global fit. Such systems are valuable for testing theories of binary star formation and understanding how the environment of a star in a close-but-detached binary affects its physical properties. In particular, we examine how a star's properties in such a binary might differ from the properties it would have in isolation.